2014
DOI: 10.1186/1472-6947-14-35
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of nursing staff towards computerisation: a case of two hospitals in Nairobi, Kenya

Abstract: BackgroundThe health sector is faced with constant changes as new approaches to tackle illnesses are unveiled through research. Information, communication and technology have greatly transformed healthcare practice the world over. Nursing is continually exposed to a variety of changes. Variables including age, educational level, years worked in nursing, computer knowledge and experience have been found to influence the attitudes of nurses towards computerisation. The purpose of the study was to determine the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
38
6
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 21 publications
18
38
6
10
Order By: Relevance
“…This indicated that healthcare workers had good experience in applications of this technology as the required tools were available and commonly used in all hospitals in Kuwait. This goes in accordance with previous studies that indicated availability of tools and applications of e-health increased the level of healthcare professionals' skills and experience (Kipturgo MK et al, 2014 andSamuel M. Et al., 2014). Comparatively, in a survey that was conducted on Indian physicians, the author reported that few of the respondents (1%) had no experience in using the computers.…”
Section: Discussionsupporting
confidence: 81%
“…This indicated that healthcare workers had good experience in applications of this technology as the required tools were available and commonly used in all hospitals in Kuwait. This goes in accordance with previous studies that indicated availability of tools and applications of e-health increased the level of healthcare professionals' skills and experience (Kipturgo MK et al, 2014 andSamuel M. Et al., 2014). Comparatively, in a survey that was conducted on Indian physicians, the author reported that few of the respondents (1%) had no experience in using the computers.…”
Section: Discussionsupporting
confidence: 81%
“…In alignment with the present study, Kivuti Wanjuki & Chepchirchir (2011) Osborne ( 2011) as they mentioned that information literacy is perceived as a major part of a nurse's professional role . Kandeel & Ibrahim( 2010), Kivuti Wanjuki & Chepchirchir ( 2011), Kipturgo et al ( 2014) as they reported that nursing students had a positive perception of the impact of using information technology education and health care, which indicate student readiness for nursing informatics education. Furthermore, study results declared that nursing students educational needs of nursing informatics include: application of informatics in education, telemedicine, ethical application in nursing ……etc.…”
Section: Discussionmentioning
confidence: 99%
“…It reveals that nurse managers had very positive attitudes towards use of computers in provision of health care. (11) 100% of nurses had positive attitudes towards computer utilization. 50.8% and 30.8% had average and fair computer skills respectively.…”
Section: Materials and Methods:-mentioning
confidence: 99%
“…Most nurse managers (69.1%) on job training in computers. (11) Computer technology has the potential to impact on the structure and delivery of healthcare, challenge the traditional roles and scope of practice, alter the existing boundaries and relationships and reinvent the clinical environment of nursing. (12) The results show that both nurses' informatics competencies and nursing computer system success do have influence on nursing organizational impact.…”
Section: Materials and Methods:-mentioning
confidence: 99%